Qualitative Study on The Role of Madrasah in Improving The Social Mobility of Students at MTs Insan Cendekia Sangatta Utara - Amina, Fitriah; Yasin, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research is about the role of Madrasah Tsanawiyah (MTs) Insan Cendekia in supporting the social mobility of students through a qualitative case study approach. This research is based on the strategic role of madrasas as Islamic educational institutions that have the potential to become agents of social change in Indonesian society. This study discusses the role of madrasas in increasing social mobility, as well as what strategies are implemented by madrasas to support the improvement of students' social mobility and the views of students, teachers, and parents regarding the contribution of madrasas to social mobility in Indonesia. This study uses a qualitative descriptive approach with a data collection method through observation, interviews with students, teachers, and parents. The results of the study show that MTs Insan Cendekia plays a role in increasing social mobility through the formation of moral character based on Islamic values, increasing academic competence, developing soft skills and social skills through extracurricular activities, as well as exposure to the professional world through internship programs and cooperation with various institutions. In addition, the madrasah strengthens student leadership and entrepreneurship and works with external parties to provide additional training. Positive views from students, teachers, and parents show that MTs Insan Cendekia is effective in supporting social mobility and student development.